Female Healthcare Workers: An Islamic Panacea - Abubakar Ibrahim Adamu; Hamidu Ardo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Due to the growing rate of the Muslim population in Nigeria put forward the need to gain a better understanding of the cultural influences of Islamic faith and health related perceptions. The research has been done in discovering the experiences of Muslim women as recipients of healthcare or in different professional settings, with little attention paid to the challenges Muslim women face as service providers within healthcare. The study also help inform healthcare organizations, practitioners, policy makers, and educators about the unique challenges Muslim women healthcare professionals face in the Nigerian environment. The paper also addresses the issues of Muslim women as healthcare practitioners in order to help initiate changes that can lead to more opportunities and exposure for Muslim women in the world and enable these professionals to provide more culturally meaningful, competent, and sensitive care personnel. The paper will provides historical development of Islam in Nigeria and also the grounds and conditions for female health workers from Islamic Perspectives; it would discuss the activities of female in healthcare centres and their impacts and the opinions of the Islamic scholars. This research work adopts analytical method. The sources include journals, published works, works of other researchers etc where consulted. It is significant to all by creating awareness among the Muslims Ummah.